Mothers' negotiation of welfare support: the emergence of privatized entitlement. Issue 11 (22nd May 2020) - Benjamin, Orly
Abstract : Purpose: Previous accounts of exclusion, primarily those proposed in the context of access to welfare, marginalize the role of negotiation and its potential for highlighting distinct barriers and possibilities within specific institutional configurations. Furthermore, when negotiation is examined in the context of access to social services, it is rarely considered as reflecting changes in exclusion or the need to distinguish among exclusionary outcomes in mothers' lives. The author proposes a conceptualization of the distinction between civic exclusion and isolated exclusion, introducing the latter as a specific condition in which mothers are forced to respond to their children's needs by resorting to privatized entitlement. Design/methodology/approach: Structured interviews were conducted between 2016 and 2017 with 90 mothers "providing in poverty" from seven marginalized categories in Israel. The interviews were analyzed using a grounded theory perspective. Findings: Three negotiation positions are revealed: positive citizenship, privatized entitlement and inconsistent gains. These positions reflect specific conditions of civic exclusion, which manifests in the form of multiple disadvantage in the lives of mothers, regardless of available forms of welfare support; and isolated exclusion, which manifests as the inability to protect one's children from harsh material scarcity, regardless of attempts to establish eligibility. Research limitations/implications: Longitudinal data could better reflect the ramifications of isolated exclusion, particularly when translated into privatized entitlement. Practical implications: The consequences of isolated exclusion should be studied, in order to prevent negotiation failure leading to this phenomenon. Originality/value: Up until recently, the notion of exclusion was used without relevant distinctions obscuring the meaning of failing to negotiate access to welfare, in mothers' lives. Conceptualizing negative outcomes of negotiation as leading to isolated exclusion and privatized entitlement clarifies the meaning of poverty as dependency. Further, without relevant distinctions, scholars' and activists' effort to introduce higher commitment to mothers' negotiation among street-level bureaucrats cannot be accounted for.